PENGEMBANGAN APLIKASI PEMILIHAN BUAH TOMAT UNTUK BIBIT UNGGUL BERDASARKAN WARNA DAN UKURAN MENGGUNAKAN HSV DAN THRESHOLDING - Maula, Ahmad Zaky; Rahmad, Cahya; Rosiani, Ulla Delfana (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Tomato is the most widely cultivated fruit in the world. The low production of tomato in Indonesia at planting tomato regardless quality. Then be directed to increase tomato quality with planting of the seed is available from the selection of good tomato quality. Science and digital image processing technology make it possible for tomato quality selection with automatically, by using application tomato fruit selection for superior seed by color and size using color space Hue Saturation Value (HSV) method and thresholding processing. From the result of application has 3 (three) output from the color and size of the fruit is good tomato, half as nice tomato and not nice tomato. Keyword : Tomato, Color, Size, Hue Saturation Value (HSV), Quantization HSV, Thresholding, Otsu Threshold, Data Similarly.